2019
DOI: 10.1534/g3.118.200803
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Affects Heme Function as a Possible Mechanism of Action

Abstract: Metformin elicits pleiotropic effects that are beneficial for treating diabetes, as well as particular cancers and aging. In spite of its importance, a convincing and unifying mechanism to explain how metformin operates is lacking. Here we describe investigations into the mechanism of metformin action through heme and hemoprotein(s). Metformin suppresses heme production by 50% in yeast, and this suppression requires mitochondria function, which is necessary for heme synthesis. At high concentrations comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…The effects of the drug include positive influences on mitochondrial respiration and activation of the 5= AMP-activated protein kinase. Recent work also indicates that MET suppresses heme production in yeast, erythrocytes, erythropoietic cells, and hepatocytes and that the drug acts to influence the redox states of heme (66). The same study and earlier work (88) indicated that ART had an even greater activity in suppressing heme levels.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The effects of the drug include positive influences on mitochondrial respiration and activation of the 5= AMP-activated protein kinase. Recent work also indicates that MET suppresses heme production in yeast, erythrocytes, erythropoietic cells, and hepatocytes and that the drug acts to influence the redox states of heme (66). The same study and earlier work (88) indicated that ART had an even greater activity in suppressing heme levels.…”
Section: Discussionmentioning
confidence: 72%
“…For example, metformin (MET) (1,1-dimethylbiguanide hydrochloride) is an FDA-approved drug for the treatment of type 2 diabetes mellitus, and MET also has antifungal activity ( 63 65 ). MET suppresses the production of heme in yeast cells, and the suppression involves functional mitochondria ( 66 , 67 ). The activity of the antimalarial drug artemisinin (ART) may involve an antimitochondrial influence as well as the generation of ROS in a heme-dependent manner ( 68 70 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alshawi and Agius (2018) report that metformin (0.1-5 mM) does not inhibit mGPD in permeabilized rodent hepatocytes. Li et al (2018) discovered that cytochrome C reduction, used as the activity reporter for mGPD in one of the assays by Madiraju et al (2014), is inhibited by metformin in a concentration-dependent (0.2-2.5 mM) manner.…”
Section: Author's Notementioning
confidence: 99%